Institutional Approach for Governance and Economic Development in Indonesia - Rani Wardaniah; Lubna Salsabila; Aqil Teguh Fathani; Timbul Dompak; Karol Teovani Lodan; Etika Khairina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
As weak policies are blamed for poor economic outcomes in many developing countries and institutions and governance have taken on a greater role in explaining policymaking, this article provides an overview of a collection of papers in the respective study on institutions, governance, and economic development in Indonesia. Many scholars assume that institutions and governance are ultimately interconnected. It is understood that if an institution in a nation is fair, the integrity of the nation's governance would also have to be decent. Therefore, such studies have never been conducted in Indonesia. This research used a descriptive qualitative approach to analyze how an institutional approach might affect Indonesia’s governance and economic development. The results of the research indicate that institutions and governance contribute an equal impact in a country's economic development. The economic development process in Indonesia is hindered by a poor governance system, exacerbated by a lack of commitment and consistency.